Blood Schizonticidal Activity and Safety of Tafenoquine When Administered as Chemoprophylaxis to Healthy, Nonimmune Participants Followed by Blood Stage Plasmodium falciparum Challenge: A Randomized, Double-blind, Placebo-controlled Phase 1b Study. (1st November 2018) - McCarthy, James S; Smith, Bryan; Reid, Mark; Berman, Jonathan; Marquart, Louise; Dobbin, Caroline; West, Leanne; Read, Lisa T; Dow, Geoff S
Abstract: Background: Tafenoquine was recently approved for chemoprophylaxis of malaria. Its specific activity against liver and blood stages of Plasmodium species has been separately characterized in animals but not in humans. Methods: In this randomized, double-blind, placebo-controlled study, 16 malaria-naive, glucose-6-phosphate dehydrogenase–normal participants aged 20–42 years received tafenoquine chemoprophylaxis prior to challenge with blood stage Plasmodium falciparum . Participants were randomly assigned to either tafenoquine (n = 12) or placebo (n = 4) and took blinded study medication (single 200-mg dose) on days 1, 2, 3, and 10, followed by intravenous inoculation with approximately 2800 P. falciparum parasitized erythrocytes on day 13. The primary endpoint was the number of participants requiring rescue treatment with artemether/lumefantrine due to the onset of parasitemia as determined by quantitative polymerase chain reaction. Results: None of the 12 participants who received tafenoquine developed parasitemia, whereas all placebo participants developed parasitemia ( P = .0005). Two cases of mild hemoglobin decrease and a single case of mild hyperbilirubinemia occurred in the tafenoquine group. Conclusions: Tafenoquine chemoprophylaxis is safe and effective in preventing malaria in healthy nonimmune participants challenged with blood stage P. falciparum . Clinical Trials Registration: Australian and New Zealand Clinical Trials Registry (ANZCTR): ACTRN12617000102370. Abstract : Previous studies show that tafenoquine is effective against Plasmodium liver stages and subsequent erythrocytic asexual stages. Confirmation of blood schizonticidal activity against P. falciparum is warranted in a nonimmune population to confirm the data from African tafenoquine studies.